Chorology : On Beginning in Plato's Timaeus. - Sallis, John (Studies in Continental thought., 2002)
In Chorology, John Sallis takes up one of the most enigmatic discourses in the history of Philosophy. The implications of the chorology are momentous and communicate with many of the most decisive issues in contemporary philosophical discussions.